Predictors of fielding performance in professional baseball players - Mangine, G. T.; Hoffman, J. R.; Vazquez, J.; Pichardo, N.; Fragala, M. S.; Stout, J. R. (International Journal of Sports Physiology and Performance, 2013)
The ultimate zone-rating extrapolation (UZR/150) rates fielding performance by runs saved or cost within a zone of responsibility in comparison with the league average (150 games) for a position. Spring-training anthropometric and performance measures have been previously related to hitting performance; however, their relationships with fielding performance measures are unknown. Purpose: To examine the relationship between anthropometric and performance measurements on fielding performance in professional baseball players. Methods: Body mass, lean body mass (LBM), grip strength, 10-yd sprint, proagility, and vertical-jump mean (VJMP) and peak power (VJPP) were collected during spring training over the course of 5 seasons (2007-2011) for professional corner infielders (CI; n = 17, fielding opportunities = 420.7 ± 307.1), middle infielders (MI; n = 14, fielding opportunities = 497.3 ± 259.1), and outfielders (OF; n = 16, fielding opportunities = 227.9 ± 70.9). The relationships between these data and regular-season (100-opportunity minimum) fielding statistics were examined using Pearson correlation coefficients, while stepwise regression identified the single best predictor of UZR/150. Results: Significant correlations (P < .05) were observed between UZR/150 and body mass (r = .364), LBM (r = .396), VJPP (r = .397), and VJMP (r = .405). Of these variables, stepwise regression indicated VJMP (R = .405, SEE = 14.441, P = .005) as the single best predictor for all players, although the addition of proagility performance strengthened (R = .496, SEE = 13.865, P = .002) predictive ability by 8.3%. The best predictor for UZR/150 was body mass for CI (R = .519, SEE = 15.364, P = .033) and MI (R = .672, SEE = 12.331, P = .009), while proagility time was the best predictor for OF (R = .514, SEE = 8.850, P = .042). Conclusions: Spring-training measurements of VJMP and proagility time may predict the defensive run value of a player over the course of a professional baseball season.